PEMBERDAYAAN MASYARAKAT MELALUI PENDAMPINGAN PEMBUATAN STIK DAUN KELOR SEBAGAI INOVASI PRODUK KESEHATAN DAN PANGAN SEHAT DI DESA BARUGBUG - Agustiawan, M.Nassir; Saepudin, Eli Apud; Hadi, Hadi Haerul; Samudra, Dian (Jurnal Abdimas Bina Bangsa, 2025)
Community empowerment through product innovation based on local potential is one of the strategic steps in improving economic welfare and public health. One of these efforts was carried out through assistance in making moringa leaf sticks in Barugbug Village. Moringa leaves are known to have various health benefits, such as being rich in vitamins and minerals, which can be utilized as raw materials for healthy food products. This program aims to provide training to the village community in processing moringa leaves into moringa sticks with selling value, as well as introducing the product as an alternative healthy snack. The method used in this program is a participatory approach, by involving the community in every stage of making the product, from material processing to marketing. The results of this program show that the community of Barugbug Village can produce moringa leaf sticks with good quality, and understand the potential market that can be accessed to increase their income. In addition, this program also has a positive impact on the community's awareness of the importance of healthy food consumption. Continuous assistance is expected to improve the community's skills in entrepreneurship and introduce local products that have high nutritional value to a wider market.